Curriculum Development in Information Studies with Special Reference to Information Technology - Parthasarathy, S.; Neelameghan, A. (Journal of Information and Knowledge, 2014)
Discusses the variety of innovations that have been developing in the sector of information technology. Delineates the areas in which IT has impact on library and information systems and services, the consequent need for fe-formulation of the modules for courses in information science, with particular reference to the Indian context. Presents a status-report on curriculum developments in information studies at the international and national levels. Present a model curriculum for information studies for under-graduate courses as well as for Post-graduate courses.